Periodontal Diseases and their Surgical Management in Dogs - Khatariya, MD; Talekar, SH; Dodia, VD; Ahlawat, AR; Kalaria, VA (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The present retrospective surveillance (n = 48) and actual dental scaling (n = 20) work were conducted on dogs of either sex from 2 to 12years in different breeds with periodontal diseases (PD) presented to the VCC, Junagadh. Among the 48 retrospective cases, the higherincidence was recorded in dogs above 6 years of age (56.25 %) followed by 3-6 years (37.5 %) and < 3 years of age (6.25 %), particularlyaffecting male dogs (70.83 %). Pomeranian/Spitz breed was affected the most (39.58 %, 19/48), followed by German shepherd (16.67%), Labrador retriever (14.58 %), non-descript (14.58 %), and other 4 to 6%. The highest incidence of stage 4 PD was noticed in thedogs of > 6 years of age (53.84 %). Among 20 dogs of the current year, the major complaint was halitosis (70 %) and sticky salivation(55 %), followed by anorexia (35 %), pawing at mouth (20 %) and facial swelling (15 %). 11 out of 20 dogs (55 %) were maintained on apurely vegetarian diet and rest 9 (45 %) on veg and non-veg diet. Oral examination of dogs revealed a varying degree of dental plaquein all 20 cases (100 %), followed by dental calculus (85 %), gingival recession (45 %), gingival hyperplasia (30 %) and tooth fracture (15%). Plaque index (PI) 2 was observed maximum in 11 (55 %) dogs, followed by PI 1 in 7 (35 %) and PI 3 in 2 (10 %) dogs. Dogs sufferedmaximum with CI 2 type calculus (45 %), followed by CI 1 (25 %) and CI 3 (20 %). Furcation of a varying degree was noticed only in8 40% dogs out of 20, which was classified as FE 1 in 4 (20 %), followed by FE 3 and FE 2 in 2 cases each (10 %). In 13 out of 20 dogs,periodontal probing depth was < 3 mm, whereas it was 4 mm and > 5 mm in 4 (20 %) and 3 (15 %) dogs, respectively. Most effectivedental scaling could be performed under diazepam-ketamine general anesthesia by using an ultrasonic piezo scaler tip at a 45° angleto the tooth surface for removal of calculus.
Keywords: Canine; Dental scaling; Dental tartar; Incidence; Periodontal disease